BUSINESS PROCESS DEVELOPMENT OF SUPPLY CHAIN SYSTEM ON E-COMMERCE LOGISTICS PROVIDER THROUGH QUALITATIVE STUDY - Zakka Ugih Rizqi; Adinda Khairunisa (Jurnal PPI Dunia, 2020)
E-commerce is growing rapidly in Indonesia. In fact, the number of e-commerce transactions in Indonesia is the largest in Southeast Asia in 2019. This has a major impact on logistics service providers because the e-commerce trading system requires logistical intermediaries between sellers and buyers. Therefore, logistics companies are developing rapidly to achieve this opportunity so that each company competes to become the best logistics company. Companies become competitive if they have a good business process. So that the effectiveness and efficiency of the supply chain are two important things so that the company becomes sustainable. This research is basically qualitative study where the business process development of PT Z is carried out to enhance the efficiency and effectiveness of the supply chain through Focus Group Discussion (FGD) and Benchmarking. Through a systematic process, more effective and efficient business process are obtained from the perspective of information flow, financial flow, and flow of goods.